Compound Risk and Crisis Assessment - Craparo, Alessandro; Minoarivelo, Henintsoa Onivola; Birner, Jana; Nguyen, Kien; Basel, Ashleigh; Läderach, Peter; Liebig, Theresa; Guariso, Daniele; Guerrero, Omar (CGIAR System Organization, 2024)
The Compound Risk and Crisis Assessment framework for instability and displacement organisations.